2014
DOI: 10.1007/s12262-014-1134-2
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Inflammatory Response in Patients with Appendicitis: a Progressive Phenomenon

Abstract: The systemic inflammatory response has been described in patients with appendicitis. However, its progression from onset of symptoms to diagnosis has not been characterized. The specific purpose of this study was to describe and characterize the systemic inflammatory response to appendicitis. A descriptive cross-sectional study was conducted. One hundred eighty-three patients were studied,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…WBCC value, CRP value, and NE% value are higher in complicated AA than in uncomplicated AA, in accordance with most previous reports (1,6,8,15,19,34). And our data also support this view.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…WBCC value, CRP value, and NE% value are higher in complicated AA than in uncomplicated AA, in accordance with most previous reports (1,6,8,15,19,34). And our data also support this view.…”
Section: Discussionsupporting
confidence: 93%
“…Laboratory tests such as white blood cell count (WBCC) and C-reactive protein (CRP) have long been used to support clinical data in the decision-making process (1,5,(11)(12)(13). And neutrophil percentage is also used in the diagnosis of AA (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Many of our patients (42.8%) had symptoms lasting 24–48 h. However, although someone could believe that the inflammatory response in AA is progressive (the longer the duration of symptoms the worse the severity of AA) [ 36 ], in our multivariate analysis it was observed that patients with duration of symptoms less than 24 h were more likely to suffer from ACA, hence why this was included in our new score. This result could be explained by the fact that in small children AA is an uncommon disease that has a varied presentation and complications that can develop rapidly, and in our study our patients with ACA were statistically younger than the patients with AUA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, computed tomography also involves exposure to ionizing radiation for children. Because appendicitis causes a systemic inflammatory response, 10 simple, widely available, and inexpensive inflammatory tests are still used to support the clinical diagnosis of appendicitis. Several studies have so far investigated a variety of inflammatory biomarkers associated with appendicitis, and numerous conflicting results have been obtained from these studies.…”
Section: Discussionmentioning
confidence: 99%